The dual nature of immunotherapy in female reproductive disorders: immune homeostasis and clinical challenges - Abulajiang, Yiliminuer; Wu, Yumei; He, Yue (Frontiers in Immunology, 2025)
The female reproductive system (FRS) exhibits unique immunological characteristics, balancing defense against pathogens with tolerance to sperm and semi-allogeneic embryos. Key players include decidual natural killer (dNK) cells, immune checkpoint molecules (ICMs) and a complex immune microenvironment (IME). Dysregulation of these elements contributes to diseases like recurrent spontaneous abortion (RSA), endometriosis, primary ovarian insufficiency (POI), and infertility. Immunotherapy, particularly immune checkpoint inhibitors (ICIs) and chimeric antigen receptor (CAR) T-cell therapy, shows significant promise in treating gynecological malignancies (e.g., cervical, endometrial, ovarian cancers), especially in advanced/recurrent settings or with specific biomarkers like mismatch repair deficiency. However, challenges persist, including limited efficacy in microsatellite stable tumors, resistance mechanisms and significant immune-related adverse events (irAEs). Critically, emerging evidence indicates potential detrimental effects of immunotherapy (especially ICIs) on female reproductive function, including diminished ovarian reserve, impaired oocyte maturation, hormonal disruption, and possible infertility, mediated by inflammatory responses, gonadotoxicity, and disruption of immune tolerance. Management of female-specific toxicities requires personalized strategies, fertility assessment, and consideration of preservation techniques. Future directions emphasize the development of predictive biomarkers, optimization of combination therapies, and implementation of truly individualized treatment regimens that account for the unique FRS IME, sex hormone influences, and the imperative to preserve fertility. Addressing the reproductive toxicity of novel immunotherapies remains a critical unmet research need.